The Existence of Optimal Control for Semilinear Distributed Degenerate Systems - Plekhanova, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
Optimal control problems for a class of semilinear distributed systems unsolved with respect to the times derivative are studied. Two types of initial condition for the system state and various cost functionals are considered in the problems. Abstract results are illustrated by examples of the start control problems for the quasistationary system of phase field equations.